2021
DOI: 10.1016/j.jmig.2021.03.007
|View full text |Cite
|
Sign up to set email alerts
|

A Clinically Applicable Prediction Model for the Risk of Transfusion in Women Undergoing Myomectomy

Abstract: We sought to identify the variables independently associated with intra/postoperative blood transfusion at the time of myomectomy. We further hoped to develop an accurate prediction model using preoperative variables to categorize an individual's risk of blood transfusion during myomectomy. Design: Case-control study. Setting: Not applicable to this study, which used the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database. Patients: Women who underwent an open/abdomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This study showed that a prediction model based on intraoperative blood loss, CRP, and urinary volume 24 h after surgery has a good accuracy to predict complications (reintervention and moderate/high postoperative blood loss) in women undergoing laparoscopic surgery for benign gynecological pathologies. Several authors have tried to define a risk model for gynecological procedures [16][17][18]. Pepin et al [18] described a model for laparoscopic hysterectomy for benign conditions based on race, history of laparotomy, history of laparoscopy, predicted preoperative uterine weight, BMI, and surgeon annual case volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that a prediction model based on intraoperative blood loss, CRP, and urinary volume 24 h after surgery has a good accuracy to predict complications (reintervention and moderate/high postoperative blood loss) in women undergoing laparoscopic surgery for benign gynecological pathologies. Several authors have tried to define a risk model for gynecological procedures [16][17][18]. Pepin et al [18] described a model for laparoscopic hysterectomy for benign conditions based on race, history of laparotomy, history of laparoscopy, predicted preoperative uterine weight, BMI, and surgeon annual case volume.…”
Section: Discussionmentioning
confidence: 99%
“…Klebanoff et al [17] formulated a predictive model to estimate the risk of blood transfusion due to intraoperative or postoperative bleeding, showing that ethnicity, surgical approach, and intraoperative blood loss are factors showing a considerable risk for requiring blood transfusion after open or laparoscopic myomectomy. Similarly, Delli Carpini et al [16], analyzing factors associated with complicated myomectomies, emphasized the value of presurgical evaluation in identifying variables that can predict intraoperative blood loss and Hb drop, such as the number of fibroids and International Federation of Gynecology and Obstetrics (FIGO) classification (at preoperative ultrasound assessment), as well as intraoperative factors such as operating time and the intramyometrial injection of diluted epinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…Te data acquisition module of the system was connected with the big data integration platform of the hospital. Te data acquisition module collected the business data of risk factors in real time, and then used the data processing module to fnally summarize and save the data to the complication database [20][21][22]. Te patient management interface includes name, gender, treatment type, treatment department, treatment date, and risk assessment results, as shown in Figure 4.…”
Section: Evaluation System Applicationmentioning
confidence: 99%
“…The most common complication is myomectomy-associated bleeding. Studies report blood transfusion rates between 4 and 20% [1,3] of patients who underwent myomectomy. Several techniques have been developed to prevent bleeding during open myomectomies: uterine artery temporary ligation, intra-myoma infiltration of vasopressin, intravaginal misoprostol or dinoprostone, the use of pro-fibrin/thrombin agents, or the use of tourniquet around the cervix or infundibulum-pelvic ligaments [4,5].…”
Section: Introductionmentioning
confidence: 99%